Fundamental research funding promotes college graduates’ employment: Evidence from the National Natural Science Foundation of China - Shilin Zheng; Peikang Zhang (China Economic Quarterly International)
Drawing on the case of the the National Natural Science Foundation of China (NSFC), we examine the impact of fundamental research funding on college graduates’ employment. Our findings indicate that an increase in total funding is positively associated with higher monthly salaries and lower unemployment rate among graduates. The NSFC funding enhances scientific research output, improves teaching and experimental facilities, and provides more research opportunities for students. This paper provides policy implications on how China can cultivate talent and promote the employment of college graduates.